(untitled) (Вісник: Міжнародні відносини, 2024)
Economic resilience (as well as global economic resilience) is comparably a new field of economic research. In comparison with stable economic development it means the ability of an economic agent to cope, recover and reconstruct after a shock or crisis. Global economic resilience means the ability of national economies, global economic actors and world economy as a whole to cope and recover after global economic shocks. To adapt to new economic challenges and shocks in XXI century world economy needs a global regulatory cooperation.